The Resilience of Smallholder Layer-Chicken Farmers Throughout the COVID-19 Pandemic: Evidence from Indonesia - Priyono; Kusumaningrum, D. A.; Rusdiana, S.; Praharani, L.; Widiawati, Y.; Kostaman, T.; Herliatika, A.; Pratiwi, N.; Azizah, N.; Iji, P. A. (Faculty of Animal Science, IPB University, 2024)
Smallholder layer-chicken farming in Indonesia is essential to ensure national food production, food security, and economic resilience. During the COVID-19 pandemic, small-scale layer-chicken farming exhibited adaptability. This study aims to assess the smallholder layer-chicken farmers resilience in Indonesia during the challenges posed by the COVID-19 pandemic. This research employed cross-sectional data collected from February to July 2023 from 114 smallholder layer chicken farmers in West Java, Central Java, and East Java using a purposive sampling technique. Data analysis used descriptive statistics, financial analysis, and the Wilcoxon Signed Rank Test. The results showed that the COVID-19 pandemic impacted the decline in the population and production of layer-chicken at the beginning of the COVID-19 pandemic but subsequently demonstrated an increase afterward. Financial analyses showed an increase in operational costs, specifically feed and labor, during the COVID-19 pandemic. The layer-chicken farms could adapt and maintain profitability amidst increasing operational costs. The findings showed that the COVID-19 pandemic significantly impacted increasing feed costs (p<0.05) and labor costs (p<0.05). The revenue-cost ratio remained relatively stable. The study also showed significant differences in profit levels before, during, and after the COVID-19 pandemic (p<0.05). Profit levels decreased during the beginning of the COVID-19 pandemic and recovered afterward, showcasing the smallholder layer chicken farmer’s resilience during the COVID-19 pandemic. These findings offer valuable insights for policy formulation aimed at fortifying the resilience demonstrated by smallholder layer-chicken farming in Indonesia amidst the challenges posed by the COVID-19 pandemic and other potential crises in the future.